Perioperative safety after cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy for pseudomyxoma peritonei from appendiceal origin: Experience on 254 patients from a single center. Issue 4 (April 2020) - Li, Xin-Bao; Ma, Ru; Ji, Zhong-He; Lin, Yu-Lin; Zhang, Jue; Yang, Zhi-Ran; Chen, Lin-Feng; Yan, Feng-Cai; Li, Yan
Abstract: Objective: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is a standard treatment for pseudomyxoma peritonei (PMP) recommended by Peritoneal Surface Oncology Group International (PSOGI). The study is to analyze the incidence of perioperative serious adverse events (SAEs) of CRS + HIPEC to treat PMP patients, and identify the risk factors, for guiding the prevention of SAEs. Methods: This is a retrospective study on the PMP database established at our center. The clinicopathological features, treatment details and SAEs information on the PMP patients are systematically established in this database. The incidence, organ system distribution and severity of perioperative SAEs are analyzed. Univariate and multivariate analyses are performed to identify the independent risk factors. Results: Among the 272 CRS + HIPEC procedures for 254 PMP patients, there are 93 (34.2%) SAEs. Six systems are involved in the SAEs, including infections (9.6%), digestive system (8.1%), respiratory system (6.3%), cardiovascular system (5.5%), hematological system (2.9%), and urinary system (1.5%), in terms of frequency. In terms of severity, the majority is grade III SAEs (27.9%), followed by grade IV SAEs (4.8%) and grade V SAEs (1.5%). Univariate analysis reveals 4 risk factors for perioperative SAEs: HIPEC regimens ( P  = 0.020), PCI ( P  = 0.025), intraoperative red blood cell transfusion volume ( P  = 0.004), and intraoperative blood loss volume ( P  = 0.002). Multivariate and logistic regression model analysis identifies only one independent risk factor for perioperative SAEs: intraoperative blood loss volume ( P  = 0.001, OR = 0.344, 95%CI: 0.182–0.649). Conclusions: PMP patients treated by CRS + HIPEC at experienced centers could have acceptable safety. Improving the surgical techniques and developing the integrated hemostasis techniques are essential to reduce intraoperative blood loss and decrease SAEs rate.